High-resolution melting PCR analysis for genotyping the gene polymorphism of TNF-α, TGF-β1, IL-10, and IFN-γ in lung transplant recipients - Zhang, HaiPing; Zou, jian; Zhang, Ji; Mu, HuiJun (Advances in clinical and experimental medicine : official organ Wroclaw Medical University, 2022)
High-resolution melting (HRM) analysis is a genotyping method which has the advantages of simple, rapid, low-cost and closed-tube operation. This study evaluated HRM analysis as an option for detecting the single nucleotide polymorphism (SNP) of cytokine, and profiled the distribution of cytokine gene polymorphism in the lung transplant recipients (LTRs). High-resolution melting-polymerase chain reaction (HRM-PCR) assays for genotyping tumor necrosis factor alpha (TNF-α) (-308 A/G), tumor growth factor beta 1 (TGF-β1) (+869 T/C), interleukin 10 (IL-10) (-592 C/A, -819 T/C, -1082 G/A), and interferon gamma (IFN-γ) (+874 T/A) SNPs were developed on the LightCycler® 480. The SNPs of the aforementioned cytokine genes in 322 LTRs and 266 normal controls were detected using HRM-PCR approach. To confirm the accuracy of the HRM-PCR assay, we randomly selected 100 samples from the LTRs and detected the aforementioned SNPs with sequence-specific primer-polymerase chain reaction (SSP-PCR) method, using a commercial kit. The data show that the HRM-PCR assay can distinguish all the cytokine SNPs, and the results of HRM-PCR analysis are in complete concordance to the genotyping results obtained using a commercial kit (κ = 1.0). Our data also show that the allele and genotype frequencies of the abovementioned cytokine are not significantly different between the LTRs and the control groups (p > 0.05). In addition, we found the genotypes of TGF-β1 +869 associated with high expression phenotype were prevalent in the LTRs. On the contrary, for TNF-α -308, IL-10 and IFN-γ, the genotypes associated with low expression phenotype were most common in the LTRs. In this study, we described a rapid, low-cost and high-throughput HRM-PCR technology for genotyping cytokine SNPs. Our data may be utilized for future studies examining the associations of cytokine gene polymorphisms with the prognosis of the LTRs.